Efeitos da interação e toxicidade das proteínas Cry1 e Vip3A de Bacillus thuringiensis em Diatraea saccharalis (Fabr., 1794) (Lepidoptera: Crambidae) - Davolos, Camila Chiaradia [UNESP] (2014)
The aim of this research was to evaluate the toxicity of different Cry1 and Vip3A proteins from Bacillus thuringiensis to Diatraea saccharalis, verify the proteins binding to receptors of the target insect and to analyze the protein interactions in larval control, seeking information to support safe and sustainable the use of transgenic Bt plants. The most toxic protein assayed was Cry1Ab followed by Cry1Ac, Vip3Aa, Cry1Ca and Cry1Fa. The population tested was not susceptible to Cry1Ea protein. Cry1Aa showed very low toxicity. Biotinylated Cry1 proteins showed specific binding to the midgut brush border membrane vesicles of the larvae. Heterologous competitive binding assays suggested a model of three receptors, a common receptor for Cry1Aa and Cry1Ab another one for Cry1Fa and Cry1Ab. Vip3Aa did not compete for binding with any of the Cry proteins tested. Among interactions bioassays, the combinations between Cry1Ab:Cry1Ca and Cry1Fa:Cry1Ca showed synergistic effect, whereas the other combinations showed antagonistic effects